PENGELOLAAN KAWASAN EKOWISATA MANGROVE DI TARAKAN - Marningot Tua Natalis Situmorang; Sulaiman Sulaiman (Program Pascasarjana Universitas Riau, 2023)
On June 25-27 2022 researchers To do research in the area Tarakan mangrove ecotourism, Tarakan City, North Borneo Province . Study this aim get diversity data types of mangroves and biophysics as well as management area Mangrove ecotourism in Tarakan. Method used is method observation direct to field and interview. Results found is there are 4 types plant dominant that grows in the region Mangrove ecotourism, namely: Avicennia marina, Rhizophora stylosa, Rhizophora mucronate, and Nypa fruticans. While the fauna that exist in the Ecotourism area Mangrove forests include Proboscis monkey ( Nasalis larvatus ), monkey Long tail ( Macaca fascicularis ), Eagle Bondol ( Haliastur indus ), King Prawns Blue ( Todiramphus chloris ), Cekakak Sungai ( Halcyon chloris ), Fan Striped ( Rhipidura javanica ), Red Cici ( Cisticola exilis ), Snake Tree ( Chrysopelea paradise ), Lizard ( Mabuya sp ), Monitor Lizard ( Varanus salvator ), Uca Crab ( Uca sp ), Crab Mangroves ( Scylla Serata ), Bees Honey ( Apis dorsata ), Mangrove Wasp ( Bruguiera parfviflora ), caterpillar Leaf ( Polyura Schreiber malayicus ), Spider ( Tetragnatha josephi ), Snails ( Gastropods ), Crabs ( Crustaceans ), Shellfish ( Bivalves ), Fish Gelodok / tempakul ( Periopthalmus ). Management of the first mangrove ecotourism area very managed service tourist Tarakan city and service income area , then by the Forestry Service North Kalimantan Province with spirit maintain and advance tour nautical as the flagship program. Ecotourism area where Public could enjoy panoramic beauty of the mangrove forest , breathe fresh air , observing animal unique, paint, photograph, be vehicle research, research and environmental education for students and students.